Brazilian Society for Food and Nutrition position statement: gluten-free diet. Issue 1 (December 2016) - Pantaleão, Lucas; Rogero, Marcelo; Amancio, Olga
Abstract Position statement: The Brazilian Society for Food and Nutrition (SBAN) bases the following position statement on a critical analysis of the literature on the indications of a gluten-free (GF) diet. (1) There is insufficient evidence to assume that healthy individuals would experience any benefits from the consumption of a GF diet. (2) Recent studies suggest that gluten sensitivity may be confounded by sensitivity to low-fermentable, poorly absorbed, short-chain carbohydrates known as fermentable oligo-, di-, and mono-saccharides and polyols (FODMAPs). (3) Epidemiological data supports that even overweight celiac disease (CD) individuals fail to achieve weight loss under a GF diet. (4) Recent experimental data showed possible deleterious effects of GF feeding on the intestinal microbiota of healthy individuals. (5) GF diets can be healthy for the general population, as long as GF-processed foods are avoided, and the ingestion of other whole grains, and low-energy-density vegetables is assured. This position statement has been externally reviewed and approved by the board of the Brazilian Society for Food and Nutrition, and has not gone through the journal's standard peer review process.